Environmental stresses on diatom and dinoflagellate morphology and community structure in the western Pacific Ocean - Yingjie Mao; Yi Long; Jiang Gui; Jun Sun (iScience)
Summary: Phytoplankton can successfully survive in specific ecological niches with their diverse morphology, and understanding morphological adaptations to the environment can better predict future phytoplankton evolution and distribution patterns. Diatoms and dinoflagellates in the western Pacific Ocean differed significantly in spatiotemporal distribution. All shapes of dinoflagellate species were more suited to higher temperatures; due to different survival strategies, diatoms adapted to the environment in a more diverse manner. Not all long-rod-shaped diatom species prefer deeper layers, and only Hyalosynedra laevigata shows an absolute growth advantage in deep water. In the relationship between the various morphological parameters of the cell, the larger the cell, the more the shape tends to be compact; cell volume increased with lengthening of the maximum linear dimension (MLD), but the slope was not unique across shape categories. These findings provide a better understanding of the role of phytoplankton morphology in the process of environmental acclimatization.